3.121. Rozwiąż równanie: a) (2x + 5) ^ 2 – x(x + 20) = 0 c) 8x * (7 – 3x) + 1 = 4(2 – x) * (x + 2) b) x(4 – x) = (2x + 3)(x – 2) + 8 d) (4 – x) ^ 2 – (2 + x) ^ 2 = x ^ 2 + 12 e) ( (2x – 1)(2x + 1) + 2 = 9x – 5x * (x + 3) f) (x – 6)(6 + x) = (4x + 3) ^ 2 – (2 – x) ^ 2

3.121. Rozwiąż równanie: a) (2x + 5) ^ 2 – x(x + 20) = 0 c) 8x * (7 – 3x) + 1 = 4(2 – x) * (x + 2) b) x(4 – x) = (2x + 3)(x – 2) + 8 d) (4 – x) ^ 2 – (2 + x) ^ 2 = x ^ 2 + 12 e) ( (2x – 1)(2x + 1) + 2 = 9x – 5x * (x + 3) f) (x – 6)(6 + x) = (4x + 3) ^ 2 – (2 – x) ^ 2